Comparison by Controlled Clinical Trial of Streptokinase and Heparin in Treatment of Life-threatening Pulmonary Embolism. Issue 5904 (2nd March 1974) - Tibbutt, D. A.; Davies, J. A.; Anderson, J. A.; Fletcher, E. W. L.; Hamill, J.; Holt, J. M.; Thomas, M. Lea; Lee, G. De J.; Miller, G. A. H.; Sharp, A. A.; Sutton, G. C.
Abstract : Treatment with heparin or streptokinase was allocated randomly to 30 patients with life-threatening pulmonary embolism verified by angiography. Treatment was given for 72 hours and pulmonary angiography was repeated. There was significantly greater (P < 0·001) evidence of thrombolysis in those patients treated with streptokinase compared with those treated with heparin. The reduction of systolic and mean pulmonary arterial pressures was also significantly greater (P < 0·05 and P < 0·02 respectively) in the streptokinase group. Seven patients failed to complete 72 hours of the trial treatment: five successfully underwent pulmonary embolectomy. Six of these "failures" had initial pulmonary angiographic scores of 24 or more and systemic systolic blood pressure recordings of 100 mm Hg or less. Patients with these features should probably be considered for pulmonary embolectomy as the initial treatment. A febrile reaction commonly occurred in the streptokinase group; otherwise side effects were no more common than in the heparin group.